2005
DOI: 10.1007/s11998-005-0012-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term weathering behavior of UV-curable clearcoats: Depth profiling of photooxidation, UVA, and HALS distributions

Abstract: The long-term weathering performance of two UV-curable clearcoat systems was studied using in-plane microtomy in combination with infrared spectroscopy, UV spectroscopy, and ESR spectroscopy. Oxygen transport characteristics were also studied using the half-time method. The photooxidation versus depth profile was highly dependant on the presence of hindered amine light stabilizers (HALS) for both coating systems. Ultraviolet light absorbers (UVA) had little effect on the photooxidation profile. A photooxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In addition, the uncertainty of the diffusion parameters and the relative humidity employed during the experiments have not been reported by Colin et al 27 The value used for the oxygen solubility could also be inaccurate. Seubert et al 57 found that oxygen solubility in UV-curable urethane acrylate clearcoats was dependent on the curing conditions. So, it can be concluded that the value used for the diffusion coefficient is presently the right order of magnitude, but somewhat low compared with expectations.…”
Section: Evaluation Of Adjustable Parameters Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the uncertainty of the diffusion parameters and the relative humidity employed during the experiments have not been reported by Colin et al 27 The value used for the oxygen solubility could also be inaccurate. Seubert et al 57 found that oxygen solubility in UV-curable urethane acrylate clearcoats was dependent on the curing conditions. So, it can be concluded that the value used for the diffusion coefficient is presently the right order of magnitude, but somewhat low compared with expectations.…”
Section: Evaluation Of Adjustable Parameters Usedmentioning
confidence: 99%
“…Schulz 1 states that numerous studies have demonstrated that oxygen diffusion in transparent polymer films is the rate-determining step and refers to experiments in pure oxygen, as opposed to air, clearly showing an effect of oxygen concentration in the gas phase on the rate of degradation. Seubert et al, 57 on the other hand, mention that the accepted belief has been that the availability of oxygen was never a rate limiting process in the photooxidation of binders, but then also show that for UV-curable urethane acrylate clearcoats the oxidation can indeed be oxygen diffusion-limited.…”
Section: 35mentioning
confidence: 99%
“…6 In some studies, the natural durability and service life of materials were increased by adding different UV absorbers (UVA), light stabilizers (HALS), colorants, etc., to resin-based coatings. [7][8][9] Some additives used as UV absorbers have provided the wood with high durability due to their high capability of UV absorption in outdoor conditions. 10 In recent years, there have been many studies on evaluating bark for preservation of wood.…”
Section: Introductionmentioning
confidence: 99%
“…The detection and characterisation of HALS within polymer‐based surface coatings have received some interest of late, as the performance and chemical activity of HALS in situ can have dramatic effects on plastic and coating performance over the lifetime of the material . Many different analytical techniques have been used for the direct detection of HALS from polymer‐based materials, the most notable being ambient mass spectrometry (MS) techniques such as atmospheric pressure – matrix assisted laser desorption ionisation (AP‐MALDI) and desorption electrospray ionisation (DESI) .…”
mentioning
confidence: 99%